Content Knowledge Mastery and Gaps of Technical Sciences Teachers in Fezile Dabi Education District - Sibanyoni, Simphiwe; Rankhumise, Mmushetji (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2023)
This study investigated subject content knowledge mastery and gaps in topics related to Technical Trades subjects of Technical Sciences teachers in the Fezile Dabi Education District. It explores the Pedagogical Content Knowledge (PCK) of Technical Sciences teachers to implement the Technical Sciences curriculum in the classroom as well as the extent of content knowledge mastery and gaps in six topics related to Technical Trades subjects. In view of previous research studies that highlighted the relationship between subject matter knowledge and PCK, a theoretical framework was developed. Researchers have identified many characteristics of ‘good’ science teaching, establishing strong links to the level and quality of content knowledge teachers hold. Subject matter knowledge that teachers master directs the content that teachers will teach and what learners will learn from the content matter prepared by the teacher. A quantitative method was used to do a case study using purposive sampling that involved teachers teaching Technical Sciences. Teachers were firstly given a questionnaire to rate themselves and were then assessed on six topics in the Technical Sciences curriculum that are related to the Technical Trades subjects across the FET phase. Statistical data analysis was used to assess findings. The research study revealed that teachers generally rated themselves as partially knowledgeable in the six topics instead of knowledgeable which is not the trend as per tests administered to them. In tests that were administered, the highest performed topic was Forces with an average of 35% and the lowest performed topic which is Viscosity and Hydraulics at an average of 15% which is an indication that teachers have subject content knowledge and PCK gaps in the six topics. The overall content mastery of teachers in these topics was 22% and content knowledge as well as PCK gaps were at an alarming 78%. A conclusion was drawn that Technical Sciences teachers struggle to understand content knowledge in the expertise of Technical Trades subjects. It was found that teachers’ level of content knowledge influences the PCK they possesses and poor subject content knowledge results in teachers being unable to effectively teach the content matter to learners, which causes poor PCK that becomes a hindrance to effective learning.